America's working women: A documentary history, 1600 to the present - Baxandall, Rosalyn Fraad, (1939- ...).; Gordon, Linda; Reverby, Susan (W.W. Norton, 1995)
A landmark work when it appeared in 1976, America's Working Women helped form the field of women's studies and transform labor history. Now the authors have enlarged the dimensions of this important anthology; more than half the selections and all the introductory material are new. Spanning the years from 1600 to the present, selections from diaries, popular magazines, historical works, oral histories, letters, songs, poetry, and fiction show women's creativity in supporting themselves, their families, and organizations or associations. Slave women recall their field work, family work, and sabotage. We see Indian women farming, and we also see the white culture coercing Indian women to give up farming. We see women in industry playing a central part in the union movement while facing the particular hazards of women's jobs and working conditions. New selections show the historical origins of today's important issues: sexual harassment, equal pay, "sex work," work in the underground economy, work in the home, and shift work. With an expanded focus on women from all racial and ethnic backgrounds and regions, America's Working Women grounds us in the battles women have fought and the ones they are in the process of winning.
Keywords: 1600-1699; 1700-1799; 1800-1899; 1900-1999; amériques; approches et analyses; cours; discipline; discours dominant; droits des femmes*; famille; his4443; histoire; histoire des femmes*; histoire et politique; inégalités; premier cycle; périodes historiques; racisme; racisme systémique; rapports sociaux de sexe; régions géographiques; sciences humaines; système colonial; systèmes d'oppressions; thématiques; travail; travail des femmes*; états-unis

Innovation technologique et pratiques domestiques : analyse d'une expérience domotique - Beillan, Véronique (Sociétés contemporaines, 1994)
À partir du suivi sociologique d'une expérience domotique portant sur quinze logements du secteur HLM, cette étude traite des conditions d'appropriation sociale d'une nouvelle technologie domestique. Après un exposé de la méthode de recueil des données, basée sur la réalisation de trois vagues ď entretiens - réparties sur trois ans - auprès des ménages du lotissement domotique, l'article présente les premiers résultats ainsi que les nouvelles pistes de recherche à approfondir lors de la troisième et dernière phase du suivi. L'analyse comparative des deux premières vagues d'entretiens a permis de noter la permanence des attentes et des attitudes des ménages à l'égard de la domotique mais aussi le caractère hétérogène et ambivalent de ces dernières. Des freins ď ordre socio-économique et socio-culturel à l'intégration sociale de la technique ont été identifiés. Ainsi, des liens se dessinent entre l'automatisation des tâches et certains éléments tels que le statut et l'identité de la femme, l'organisation et la hiérarchisation des activités domestiques, les pratiques de délégation et ď externalisation du travail domestique.
Keywords: 1900-1999; 1980-1989; 1990-1999; approches et analyses; care; cours; discipline; europe; france; inégalités; postmodernisme; premier cycle; périodes historiques; régions géographiques; sciences humaines; soc2051; sociologie; systèmes d'oppressions; thématiques; travail; travail domestique